On Paracompact and Perfectly Zero Dimensional Spaces by Using Semi Feebly Open Sets - Ghazwan Farhan Shaker; Raad Aziz Hussain AlAbdulla (Genius Journals, 2022)
The aim of this paper is to introduce contains definitions of paracompact , sfparacompact , perfectly zero- dimensional spaces , sf-perfectly zero- dimensional spaces, perfect mapping and sf − perfect mapping and we will explain the relationship among them
Keywords: paracompact; sf-paracompact; perfectly zero-dimensional